Status of sea turtle populations and its conservation at Bird’s Head Seascape, Western Papua, Indonesia - RICARDO F. TAPILATU; HENGKI WONA; PETRUS P. BATUBARA (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Tapilatu RF, Wona H, Batubara PP. 2017. Status of sea turtle populations and its conservation at Bird’s Head Seascape, Western Papua, Indonesia. Biodiversitas 18: 129-136. Bird’s Head Seascape region in the northwest of Papua contains the world’s highest marine biodiversity. The area is a unique site which contains a full range of marine and coastal habitats that are important for the breeding, foraging and migration of several species of sea turtles. This survey aimed to characterize critical habitats that are in use by sea turtles across Yapen, Wondama, Manokwari and Kaimana at Bird’s Head Seascape and to assess existing and potential threats to both habitats and population. Eight beaches were inspected for evidence of nesting and predation and anecdotal information was collected through interviews with 121 fishermen at 23 villages.  The survey confirmed the occurrence of hard-shelled turtles: Green (Chelonia mydas), Olive-ridley (Lepidochelys olivacea) and Hawksbill (Eretmochelys imbricata) nesting and foraging populations. In addition, the critically endangered leatherback turtle (Dermochelys coriacea) is occasionally seen by fishermen. Sea turtles have long been a source of protein for locals. The predictability of the timing and location of turtle abundance exposes nesting populations to long-term subsistence exploitation that cannot be sustained by these populations. Protection of significant rookeries is seen as the best conservation option for sea turtles in the Bird’s Head Seascape region. It is strongly recommended that these areas should be considered in any conservation initiative in order to maintain the sustainable population (s) in the Bird’s Head Seascape. Keywords: Bird’s Head Seascape, Chelonia mydas, conservation, Dermochelys coriacea, Eretmochelys imbricata, Lepidochelys olivacea